Surgical research - Souba, Wiley W.; Wilmore, Douglas W. (Douglas Wayne), 1938- (Academic Press, 2001)
With the recent changes in the health care industry, surgeons face increasing pressure to devote their time to their clinical activities, thus limiting their research efforts. It is essential that young and creative individuals are encouraged to perform research and are given incentives to participate in research under the mentorship of more experienced research investigators. Surgical Research is the first book to include all the information necessary for the surgical scientist to perform a research experiment. The editors have assembled outstanding, expert investigators in multiple surgical fields and asked them to describe how they achieve their research accomplishments. In Surgical Research, these experts in the field have outlined everything involved in preparing and conducting a research project. Some of the topics covered in the book include how to state a research question, how to review the available information, how to write research protocol, how to obtain grant money for the experiment, how to analyze the data, and how to present the findings. Also discussed are the ethics of animal and human experimentation along with the history and philosophy of surgical research. To continue to advance technologies and surgical methods, research must continually be performed. Potentially great discoveries are being missed because would-be researchers do not know where to start or how to conduct research, and therefore do not even try. This book provides prospective researchers with all the basic steps needed to perform a research experiment in the surgical field. No student, resident, or fellow should start a research project without this book and no senior surgical scientist should be without it occupying a prominent position in the library. Key Features * The first complete compendium detailing the process and procedures to perform surgical research * Provides details on and compares various methodologies * A "must have" resource for the surgical resident, fellow, or scientist * Includes a listing of resources and web sites to help the researcher even further